Genotypic identification of extended spectrum Î²-lactamase producing Escherichia coli in dairy supply chain - Kumar, Amarjeet; Mallappa, Rashmi Hogarehalli; Jaswal, Avinash; Kumar, Brijesh; Kumar, Naresh; VISHWESWARAIAH, RAGHU HIRIKYATHANAHALLI (Indian Journal of Dairy Science, 2021)
Foodborne illnesses due to antibiotic-resistant bacteria represent a major public health problem in both developed and developing countries. Among 190 samples, 139 Escherichia coli positive isolates from raw milk, pasteurized milk, and human handlers were identified by phenotypic methods and genotypic methods. All E. coli isolates were found to be resistant to penicillin, oxacillin, erythromycin, and clindamycin. The dominant type of resistance to cefotaxime and amoxiclav identically detected in 18.7% isolates followed by ampicillin in 17.98%, trimethoprim 15.82%, tetracycline 10.79%, nalidixic acid 7.91%, and piperacillin 7.79%. Four isolates have shown resistance (2.87%) to Ceftriaxone and ceftazidime, Cefotaxime and one isolate has shown resistance to Cefepime. Further, all four isolates were confirmed as extended-spectrum Î²-lactamase (ESBL) producer by double disc diffusion test and ESBL chromogenic medium. Later, all four isolates were evaluated by PCR and they are observed as carrier of blaCTX M gene which is responsible for ESBL antibiotic resistance in E.coli but blaTEM and blaSHV genes were absent in all four ESBL isolates. Based on the above findings, it is concluded that ESBL antibiotic resistance in E. coli were more prevalent in milk and this may due to the spread and acquirement of antibiotics resistance gene by plasmid and mobile genetic elements.